Analisis Kepuasan Konsumen terhadap Kualitas Pelayanan Parkir di Mega Mall A. Yani Pontianak - Chronika, Lidia; Mangunsong, Lamria; -, Narsih (Universitas Brawijaya, Indonesia, 2009)
This research in the form of research survai to visitor in shopping centre in A . Yani Mega- Mall using service park managed in wroughtly by managemen is A.Yani Mega- mall . Freshment Visitor becoming especial attention from party of service park always try to give the best service to each;every visitor. Visitor of shopping centre asked by its opinion hit the service quality park which is in the form of amenity park the , worker performance park the, performance of geometric space park the , security, freshment and according to tariff park the. Data got and changeable for the visitor of using to use the car wheel four residing in in building as much 100 responder. Result of research indicate that more than 50 % responder lick lips with the performance and service quality park, but for the amenity of park the responder which lick lips less than 50 . result of examination Mann- Whitney Wilc oxon prove that responder feel there no except to service quality difference of geometric space park the nya. And from calculation result mount the mean importance of every variable; with the scale 1 until 5 got by that service quality park in Security facet take possession of the highest sequence and amenity park to take possession of the underest sequence. Pursuant to the research result inferential amenity element park this become important to be paid attention to by its improvement by organizer park the shopping centre especially in Megamall A. Yani of besides important other; dissimilar element to be defended its quality.Keywords: Mega Mall,Parking,Fasilities